Evaluación de la alimentación y desarrollo de pollos broiler con suplementación de ajo (allium sativum) al 2% y 3% en el balanceado en la Parroquia La Matriz del Cantón Saquisilí - Zumba Mera, Norma de las Mercedes (2015)
This research was performed in order to assess the supply and development of broiler chickens with garlic supplementation (Allium sativum) at 2% and 3% in the ready meal in the parish La Matríz of Saquisilí Canton. The used methodology was experimental, with a completely random design. 90 cob chickens were selected, 500 no classified of 1 day of age and put in 3 compartments, in groups of 30 animals completely random, the compartments were identified according to the corresponding addition of garlic, identified as T0 (testigo) T1 (ready meal plus 2% of garlic) and T2 (ready meal plus 3% of garlic)....